Exploring the spatio-temporal patterns and driving forces of ecological resource flows in China for post-epidemic sustainable development - Wenpeng Du; Xiaozhi Xiang; Chao Zhang; Huimin Yan; Zhong’en Niu (Resources, Environment and Sustainability)
In the post-epidemic era, the domestic market as the mainstay in China is signifying a shift whereby interregional trade supersedes international trade as the pivotal driver of regional sustainable development. Thus, the scientific understanding of interregional natural resource flows within China is crucial. This study refers to the human appropriation of net primary production (HANPP) framework to construct indicators to extend the multi-regional input–output (MRIO) table. This table is then used to explore the interprovincial flow patterns and their determinants of ecological resources in China. The results show that: (1) Ecological resource flow in China predominantly moves from western inland regions to eastern coastal regions, yet the interplay among provinces is evolving into a more intricate pattern. (2) Agricultural production intensity, ecological resource endowment, and geographic distance are consistent and significant factors influencing ecological resource flow patterns. (3) Structural adjustments in ecological resource production or consumption primarily drove changes in net ecological resource flows from 2012 to 2017. Production structural changes in nearly half of the provinces initiated a decoupling of economic development from ecological resources. Meanwhile, consumption structural changes in economically developed provinces steered regional consumption patterns towards greater sustainability. These insights can offer scientific support for the integration of interregional ecological resource mobilization pathways for regional sustainable development in China.